14 day sequential therapy versus 10 day bismuth quadruple therapy containing high-dose esomeprazole in the first-line and second-line treatment of Helicobacter pylori: a multicentre, non-inferiority, randomized trial. (29th May 2018) - Liou, Jyh-Ming; Chen, Chieh-Chang; Fang, Yu-Jen; Chen, Po-Yueh; Chang, Chi-Yang; Chou, Chu-Kuang; Chen, Mei-Jyh; Tseng, Cheng-Hao; Lee, Ji-Yuh; Yang, Tsung-Hua; Chiu, Min-Chin; Yu, Jian-Jyun; et al.
Abstract: Background: Whether extending the treatment length and the use of high-dose esomeprazole may optimize the efficacy of Helicobacter pylori eradication remains unknown. Objectives: To compare the efficacy and tolerability of optimized 14 day sequential therapy and 10 day bismuth quadruple therapy containing high-dose esomeprazole in first-line therapy. Methods: We recruited 620 adult patients (≥20 years of age) with H. pylori infection naive to treatment in this multicentre, open-label, randomized trial. Patients were randomly assigned to receive 14 day sequential therapy or 10 day bismuth quadruple therapy, both containing esomeprazole 40 mg twice daily. Those who failed after 14 day sequential therapy received rescue therapy with 10 day bismuth quadruple therapy and vice versa. Our primary outcome was the eradication rate in the first-line therapy. Antibiotic susceptibility was determined. ClinicalTrials.gov: NCT03156855. Results: The eradication rates of 14 day sequential therapy and 10 day bismuth quadruple therapy were 91.3% (283 of 310, 95% CI 87.4%–94.1%) and 91.6% (284 of 310, 95% CI 87.8%–94.3%) in the ITT analysis, respectively (difference −0.3%, 95% CI −4.7% to 4.4%, P = 0.886). However, the frequencies of adverse effects were significantly higher in patients treated with 10 day bismuth quadruple therapy than those treated with 14 day sequential therapy (74.4% versus 36.7% P < 0.0001). The eradication rate of 14 day sequential therapy in strains with and without 23S ribosomal RNA mutation was 80% (24 of 30) and 99% (193 of 195), respectively ( P < 0.0001). Conclusions: Optimized 14 day sequential therapy was non-inferior to, but better tolerated than 10 day bismuth quadruple therapy and both may be used in first-line treatment in populations with low to intermediate clarithromycin resistance.